An Observational Study Of Using Lactate Dehydrogenase As Prognostic Marker In Dengue Patients - Vineela, R. H. P. V.; S. V, Srinivasa.; Lokesh M, Lokesh M (Journal of Neonatal Surgery, 2025)
Dengue infection is a febrile illness caused by one of 4 serotypes of dengue virus which is transmitted by mosquito named aedes aegypti or aedes albopictus. Dengue is also called as “break bone fever”. Most patients with dengue are asymptomatic/ mildly symptomatic. Some patients may present with severe form known as Dengue Shock Syndrome which is life threatening. LDH enzyme is usually high in states with high reticuloendothelial activity. Pathogenesis of dengue infection is directly related to level of reticuloendothelial activity, thrombocytopenia. This study will be done to analyze the relation between serum lactate dehydrogenase with severity of dengue and predicting complications Introduction: Dengue is a febrile illness caused by infection with one of four dengue viruses (DENV) transmitted by Aedes aegypti or Aedes albopictus mosquitoes. Infection may be asymptomatic or present with a broad spectrum of clinical manifestations which include mild febrile illness to a life-threatening dengue shock syndrome. Numerous viral, host, and vector factors are thought to impact risk of infection, disease, and disease severity. There are four closely related but serologically distinct DENV types of the genus Orthoflavivirus, called DENV-1, DENV-2, DENV-3, and DENV-4. There is transient cross-protection among the four DENVs, which wanes and disappears over the months following infection. Therefore individuals living in a dengue-endemic area with all DENV types cocirculating are at risk for infection with any and all DENV types. Materials And Methods: Study Design: open labelled, observational prospective study Study period: 3 months Sample size: 30patients Study area: L. Jalappa Hospital Study population: All patients > 18yrs age who are serologically tested dengue positive and admitted to R. L. Jalappa Hospital, Kolar. Results The age of the study population varied between 40-68 years. Male patients were 58% and female patients were 42% of the study population. Of the 30 patients studied most of them have complications related to dengue fever. Serum LDH levels in patients with complications was higher compared to those without complications. Serum magnesium levels is proportional to severity of complications in patients with dengue fever. Conclusion Serum LDH levels were higher in patients with complications. Patients with severe complications had relatively higher serum LDH levels compared to those with mild and moderate complications.